Synthesizing and Using Iron Oxide Nanoparticles as Nanocomposite in Cotton Fabrics Nanofinishing (Baghdad Science Journal, 2024)
Metal oxide nanoparticles, including iron oxide, are highly considered as one of the most important species of nanomaterials in a varied range of applications due to their optical, magnetic, and electrical properties. Iron oxides are common compounds, extensive in nature, and easily synthesized in the laboratory. In this paper, iron oxide nanoparticles were prepared by co-precipitation of (Fe+2) and (Fe+3) ions, using iron (II and III) sulfate as precursor material and NH4OH solution as solvent at 90°C. After the synthesis of iron oxide particles, it was characterized using X-ray diffraction (XRD), infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). These tests confirmed the obtaining of iron oxide nanoparticles with a crystalline structure in the form of (spinel), and the size of nanoparticles ranging from 13-24 nm.Iron oxide and polyaniline nanocomposite were used to apply in cotton fabrics. The iron oxide nanoparticles were dispersed with different percentage concentrations 0.5, 1, 2, 5, and 10% in the polymeric solution. Then the cotton samples were treated with the prepared nanocomposite. The electrical conductivity was measured using the four probes method, and it was found that the treated cotton fabrics acquired the electrical conductivity that they did not have before. The ultraviolet transmittance of the treated samples was also measured, and it was noted that the transmittance of the treated samples decreased compared to the untreated sample due to the absorption of ultraviolet rays by iron oxide particles, especially in the UVC field.